Killed First Burned After Attempting to Eliminate Victims of Homicide by Burning - Doğan, Kamil Hakan; Demirci, Şerafettin; Koç, Sermet (The Bulletin of Legal Medicine, 2011)
Killers commit methods such as burning, burying to deserted places and throwing the corpses into the sea or the rivers in order to eliminate corpses of the victims of homicide or to avoid recognition of the victims of homicide. If such cases are encountered, regardless of how much time passed after death, the autopsy must be done in detail and very carefully and all findings should be evaluated for identification of victim and cause of death. In this study, victims who were burned after homicide and whose autopsies were performed by the Directorate of Konya Branch of Forensic Medicine Konya in Konya city center and in districts of Konya by a forensic expert districts between 2000-2008 were evaluated. A total of 10 cases were identified during the period of examination. The age of victims ranged between 16 and 5 8 years and the average age was 3 5± 13 years. In terms of murder methods, the most commonly used method was I igature strangulation in three cases. Six victims were burned in open land. If burnt corpses are extracted from fire or encountered at the external environment, it should be investigated that the victim suffered the bums before or after death. If the person is first killed and then burned, hyperemia, congestion and soot in the respiratory tract may not be observed at autopsy which may arise with exposure to bum during the life. For the determination ofthe origin in such cases a complete and accurate death scene investigation and a thorough autopsy should be performed, genetic analysis should be done for the identification of victim and the cause of death needs to be determined. Keywords: Homicide, burns, forensic medicine